1997
DOI: 10.1029/97wr00857
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase flow modeling of a crude‐oil spill site with a bimodal permeability distribution

Abstract: Abstract. Fluid saturation, particle-size distribution, and porosity measurements were obtained from 269 core samples collected from six boreholes along a 90-m transect at a subregion of a crude-oil spill site, the north pool, near Bemidji, Minnesota. The oil saturation data, collected 11 years after the spill, showed an irregularly shaped oil body that appeared to be affected by sediment spatial variability. The particle-size distribution data were used to estimate the permeability (k) and retention curves fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 39 publications
1
69
0
Order By: Relevance
“…The estimated hydraulic conductivity was 7.02 Â 10 À 5 m/s, about an order of magnitude higher than the geometric mean conductivity of 5.6 Â 10 À 6 m/s obtained from particle-size-distribution estimates (Dillard et al, 1997). This suggests that the plume concentration distribution is a reflection of flow in the high conductivity channels within the heterogeneous porous medium, and/or that conductivities estimated from particle size distributions may underestimate large-scale aquifer hydraulic conductivity.…”
Section: Parameter Estimatesmentioning
confidence: 52%
See 1 more Smart Citation
“…The estimated hydraulic conductivity was 7.02 Â 10 À 5 m/s, about an order of magnitude higher than the geometric mean conductivity of 5.6 Â 10 À 6 m/s obtained from particle-size-distribution estimates (Dillard et al, 1997). This suggests that the plume concentration distribution is a reflection of flow in the high conductivity channels within the heterogeneous porous medium, and/or that conductivities estimated from particle size distributions may underestimate large-scale aquifer hydraulic conductivity.…”
Section: Parameter Estimatesmentioning
confidence: 52%
“…An average value of n of 3.98 was estimated using observed particle-size distributions and the methods of Essaid et al (1993) and Dillard et al (1997). Water relative permeabilities ranged from 0.02 in the highest oil saturation core of the oil body to close to 1.0 in the low oil saturation edges of the oil body.…”
Section: Flow Initial and Boundary Conditionsmentioning
confidence: 99%
“…Heterogeneous permeability values based on geostatistical interpolation of grain size data are available from Dillard et al [1997] down to an elevation of 421 m and over a 120 m horizontal interval of our domain. Permeability values were replicated to cover our computational domain and converted to saturated hydraulic conductivity.…”
Section: 1002/2015wr016964mentioning
confidence: 99%
“…The domain was discretized into 4.3 m (horizontal) by 0.47 m (vertical) grid cells allowing efficient computation of multicomponent kinetic simulations. The homogeneous porosity is assigned to be 0.38, which is the mean value determined for the north pool area [Dillard et al, 1997]. Longitudinal and transverse dispersivity were set to 1 and 0.04 m, respectively.…”
Section: Model Domain and Flow Modelmentioning
confidence: 99%
“…And unstructured grids are used too; the EquiSize Skew and EquiAngle Skew in detection are 0.52 and 0.43, respectively. It is indicated that the grids generated are simple, of high quality, and suitable [12].…”
Section: Model Reconstructionmentioning
confidence: 99%